The Dynamics of Abortion Treatment as an Effort of Harmonization between the Modern and the Traditional Medical System - Hanifatus Salwa (Antropologi Indonesia, 2020)
This article explored the phenomenon of abortion within which a health issue is embedded, both in modern medicine and traditional medicine which is very close to the culture of the local community. It described efforts of abortion treatment that act as a bridge between the roles of modern medicine and traditional medicine in the Yogyakarta region. Apart from the stigma of local community regarding abortion by women with unwanted pregnancy, this article aimed to eliminate inappropriate conceptions and practices that stem from misinterpretations of developments in science, technology, and media. Abortion at least represents a narrative and context in the medical studies, as well as opens up space for discussing the concept of women’s body health. The phenomenon of handling abortion in Yogyakarta with the ‘home abortion’ system through advertisements for ‘late menstruation’ or ‘late months’ has become part of the issue of women’s reproductive health. This step of self-abortion finally emerged with its optimism as a form of harmonization between modern medicine and traditional medicine in a broader context.